Nature and cities the ecological imperative in urban design and planning - Steiner, Frederick 1949-; Thompson, George F. 1954-; Carbonell, Armando 1951- (The Lincoln Institute of Land Policy, 2016)
"A compilation of essays by leading international landscape architects, city planners, urban designers, and architects about the need for ecological urban design. Chapters explore the economic, environmental, and public health benefits of integrating nature more fully into cities, including urban green spaces, streetscapes, and buildings"...
Includes bibliographical references and index
Keywords: Stadtplanung; Umwelt; City planning -- Environmental aspects; Sustainable urban development; Ökologie; Naturraum; Aufsatzsammlung